Lateral Meniscal Allograft Transplantation With Bone Block and Suture-Only Techniques Partially Restores Knee Kinematics and Forces. Issue 10 (August 2019) - Novaretti, João V.; Lian, Jayson; Sheean, Andrew J.; Chan, Calvin K.; Wang, Joon H.; Cohen, Moises; Debski, Richard E.; Musahl, Volker
Background: The ability of lateral meniscal allograft transplantation (MAT) to improve knee stability and the meniscal load-bearing function in patients after meniscectomy is critical for surgical success. Purpose: To compare the effects of 2 lateral MAT fixation techniques—bone block and suture only—on knee kinematics and forces. Study Design: Controlled laboratory study. Methods: With a robotic testing system, loads were applied during flexion on 10 fresh-frozen cadaveric knees: 134-N anterior tibial load + 200-N axial compression, 5-N·m internal tibial + 5-N·m valgus torques, and 5-N·m external tibial + 5-N·m valgus torques. Kinematic data were recorded for 4 knee states: intact, total lateral meniscectomy, lateral MAT bone block, and lateral MAT suture-only fixation. In situ force in the anterior cruciate ligament and resultant forces in the lateral meniscus and in the meniscal allograft were quantified via the principle of superposition. A repeated measures analysis of variance was used to analyze variations in kinematics and forces at 0°, 30°, 60°, and 90° of knee flexion. Significance was set at P < .05. Results: When anterior loads were applied, a decrease in medial translation of the tibia that was increased after total lateral meniscectomy was observed at 30°, 60°, and 90° of knee flexion for both the lateral MAT bone block (54.2%, 48.0%, and 50.0%) and the MAT suture-only (50.0%, 40.0%, and 34.6%) fixation techniques ( P < .05). Yet, most of the increases in knee kinematics after lateral meniscectomy were not significantly reduced by either lateral MAT technique ( P > .05 for each MAT technique vs the total lateral meniscectomy state). Resultant forces in the meniscal allograft were 50% to 60% of the resultant forces in the intact lateral meniscus in response to all loading conditions at all flexion angles ( P < .05). Overall, no significant differences between lateral MAT techniques were observed regarding kinematics and forces ( P > .05). Conclusion: Lateral MAT partially restored medial translation of the tibia, and the resultant forces in the meniscal allograft were only 50% to 60% of the intact lateral meniscus forces in the cadaver model. In the majority of testing conditions, no significant changes of the in situ force in the anterior cruciate ligament were observed. Surgeons should consider the potential benefits of lateral MAT when deciding the appropriate treatment for symptomatic patients after lateral meniscectomies. Both lateral MAT techniques functioned similarly. Clinical Relevance: The load-bearing function of the meniscal allograft observed in this study may be beneficial in ameliorating the short- and long-term disability associated with lateral meniscal deficiency.